Fluid-Structure Interaction Analysis of Carotid Artery Blood Flow. A Patient-Specific Investigation of the Impact of Arterial Wall Deformation on Hemodynamics. - Nordenström, Simon (My University, 2022)
Cardiovascular disease, predominantly caused by atherosclerosis, is the leading cause of death worldwide. Therefore, scientific methods capable of accurately evaluating risk factors of cardiovascular disease on a patient-specific basis are highly soughtafter. Typically, numerical approaches for simulating blood flow assume arterial walls to be rigid structures. However, to obtain more physiologically realistic simulations, the interplay between wall deformation and blood flow, the so-called fluidstructure interaction (FSI), must be taken into consideration. In this project, a workflow is established for performing patient-specific FSI simulations of blood flow and arterial wall deformation in the carotid artery – the main source of blood supply to the brain. The workflow is primarily intended to aid in the execution of FSI analyses in the STAR-CCM+ simulation software. Furthermore, the impact of FSI on hemodynamic parameters such as flow velocity, wall shear stress, and oscillatory shear index, is quantified and analyzed for a patient-specific geometry. It is shown that a rigid wall assumption results in underestimations of the areas associated with an increased risk of atherosclerosis, namely regions of low time-averaged wall shear stress and high oscillatory shear index. Moreover, the rigid wall assumption leads to overestimations of the flow velocities during the systolic phase of the cardiac cycle. FSI analyses are performed using three different material models: an isotropic linear elastic model, a Neo-Hookean model, and a Mooney-Rivlin model. For the specific boundary conditions and parameter values employed, marginal differences are observed in the hemodynamics between the three material models.
Keywords: FSI, Carotid artery, Simulation, Hemodynamics,Workflow, STAR-CCM+.